The Implementation of English Teaching and Learning in Al Khodijah Dormitory of Sunan Drajat Islamic - Shohiyah Shobaha (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2023)
It has been commonly known that in this era, many Islamic boarding schools are trying to provide English learning program in order to improve the quality of Islamic boarding school graduates. Many studies have been conducted to observe how English learning is run in Islamic boarding school to succeed the goal in mastering English for the students. This present study would like to complete the previous studies by conducting the investigation on how English learning process in Al Khodijah Dorm and what are the obstacles faced by the teachers and students during running the English dormitory programs. This research employed qualitative methodology to describe the whole data got by using observation, documentation and interviews as the instruments of studies. This recent study found that to succeed the English learning and teaching activities in Al Khodijah dorm, it was conducted the interesting morning English program. English materials, English learning media, English area and the assessment has also been settled well by the language department of Sunan Drajat Islamic Boarding School to support students’ English learning. They obstacles faced by the students and tutors were concluded by two kinds of problem namely difficulty of time managing to learn and lack of motivation to learn English.